2015
DOI: 10.11114/jets.v4i1.1081
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationship between Attachment Styles and Facebook Addiction

Abstract: Social networking sites have started to become one of the most frequently used online communication types in the world. It is reported that one of the commonly used social networking sites is Facebook. Since Facebook use is new yet, it can be stated that researches on the Facebook addiction are at the beginning level. For this reason, determining factors leading to the Facebook addiction has gained importance. In this context, in this study, relationships between attachment styles and the Facebook addiction we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 41 publications
(50 reference statements)
1
19
0
2
Order By: Relevance
“…Authors have reported that secure attachment orientation negatively predicts social media addiction (Monacis et al 2017a), and internet addiction (Eichenberg et al 2017;Monacis et al 2017a). This is in line with the negative association found between secure attachment, Facebook time, and Facebook addiction (Bashir et al 2017;Eroglu 2015;Rao and Madan 2012). Moreover, it has been assumed that stronger parental attachment is related to lesser need to use the internet (Yang et al 2016) for the purpose to escape (Soh et al 2014), and studies have concluded that it may be considered a protector factor (Eichenberg et al 2017;Savcı and Aysan 2016;Mazaheri Nejadfard and Hosseinsabet 2017;Kozan et al 2016).…”
Section: The Influences On Internet Engagement and Its Most Used Assementioning
confidence: 60%
See 2 more Smart Citations
“…Authors have reported that secure attachment orientation negatively predicts social media addiction (Monacis et al 2017a), and internet addiction (Eichenberg et al 2017;Monacis et al 2017a). This is in line with the negative association found between secure attachment, Facebook time, and Facebook addiction (Bashir et al 2017;Eroglu 2015;Rao and Madan 2012). Moreover, it has been assumed that stronger parental attachment is related to lesser need to use the internet (Yang et al 2016) for the purpose to escape (Soh et al 2014), and studies have concluded that it may be considered a protector factor (Eichenberg et al 2017;Savcı and Aysan 2016;Mazaheri Nejadfard and Hosseinsabet 2017;Kozan et al 2016).…”
Section: The Influences On Internet Engagement and Its Most Used Assementioning
confidence: 60%
“…Attachment avoidance has been reported to have no significant relationship with Facebook attachment (Oldmeadow et al 2013;Andangsari et al 2013) and Facebook addiction (Eroglu 2015;Lin 2016). Furthermore, participants high in attachment avoidance have been found to be less likely to be happy about their Facebook profile (Oldmeadow et al 2013).…”
Section: The Role Of the Attachment Theory In The Most Used Scalesmentioning
confidence: 99%
See 1 more Smart Citation
“…The exponential growth of social media, an outcome of a 21 st Century technological explosion, provides easy access to communications, socialization, and self-fulfillment (Eroglu, 2015). Facebook, the most commonly used social media site across the globe, is now recognized by researchers as an addictive behavior amongst female higher education students, with individuals experiencing withdrawal symptoms when they attempt to reduce the amount of hours spent in the application (Eroglu, 2015;Thompson, & Lougheed, 2012).…”
Section: The Underserved and Marginalized Femalementioning
confidence: 99%
“…Maintaining these online friendships becomes a critical function of everyday life, as students find self-fulfillment in seeking like-minded individuals to share and validate personal ideas and beliefs ( Eroglu, 2015;Thompson et al, 2012). For example, within Facebook, an "I hate Math" group was created to promote math failure as a socially acceptable outcome since "likes" on the page demonstrated that math failure is experienced by many people, and through a "communal camaraderie" (Aydin, 2012(Aydin, , p. 1097, it provide credibility to unsuccessful outcomes (Whyte & Anthony, 2012).…”
Section: The Underserved and Marginalized Femalementioning
confidence: 99%